فعالية استخدام الوسيلة التعليمية ”تعبير الصور" في اكتساب مهارة الكلام - Nadiroh, Nurlaila; Wijaya, Tahir; Usman, Soraiya (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2022)
This research is motivated by the condition of students who have difficulty honing their speaking skills using Arabic. With the existence of shuwar mascara media, it is hoped that it can be a fun method for students so that it can increase students' motivation to learn. This research is a quantitative research. The research method used is an experimental method using non-sampling which totals 24 students at MTS Al-wathoniyah 43 Jakarta, and is equipped with data collection techniques, observations, interviews, documents, pre and post test results. The results of the T test are used to find out whether there is a difference between two samples. From this data, the T-table was obtained at 2,069 while the T-score was 23,675. The results of the study showed that there was an influence of image description media in the acquisition of speaking skills on pre and post test data. It is known that the Sig-(2-tail) value is 0.004 < 0.05 so it can be concluded that there is an influence on the effectiveness of the application of picture description learning media in the acquisition of speaking skills of 7th grade students of MTS Al-wathoniyah Jakarta.